2013
DOI: 10.21059/buletinpeternak.v37i2.2431
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Potensi Pengembangan Usaha Peternakan Sapi Perah Dengan Menggunakan Paradigma Agribisnis Di Kecamatan Musuk Kabupaten Boyolali

Abstract: INTISARIPeningkatan populasi sapi perah dapat dilakukan pada sebuah daerah didukung potensi dari daerah tersebut. Potensi-potensi daerah untuk pengembangan sapi perah dapat ditingkatkan dengan penyediaan ketersediaan pakan, pengetahuan peternak, permintaan susu, pendapatan peternak, infrastruktur pasar, peranan lembaga pemberi kredit dan kebijakan pemerintah lokal. Tujuan penelitian ini untuk menentukan kondisi subsistem agibisnis sapi perah di Kecamatan Musuk, dan faktor faktor yang mempengaruhi pendapatan sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 1 publication
0
16
0
12
Order By: Relevance
“…Meanwhile, Halolo et al (2013a) stated that the dairy farm business was profitable and Halolo et al (2013b) stated that the dairy farm was efficient. Santosa et al (2013) revealed that the R/C ratio of dairy farm was 1.28.…”
Section: Characteristics and Business Performance Of Dairy Farm Of Mpmentioning
confidence: 99%
“…Meanwhile, Halolo et al (2013a) stated that the dairy farm business was profitable and Halolo et al (2013b) stated that the dairy farm was efficient. Santosa et al (2013) revealed that the R/C ratio of dairy farm was 1.28.…”
Section: Characteristics and Business Performance Of Dairy Farm Of Mpmentioning
confidence: 99%
“…Milk and meat production are rapidly rising in order to increase of population, economic growth, improved education levels and farmers's prosperity. To compensate for the level of farm product, the efforts focused on optimizing productivity and reproducibility of livestock, with the ability to suppress the morbidity or mortality of livestock and the spread of disease (Sutama 2008;Santosa et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pengembangan usaha ternak melalui peningkatan populasi sapi perah dapat dilakukan pada suatu daerah yang didukung oleh potensi daerah tersebut. Potensi daerah untuk pengembangan sapi perah dapat ditingkatkan dengan penyediaan pakan, pengetahuan peternak, permintaan susu, pendapatan peternak, infrastruktur pasar, peranan lembaga pemberi kredit, dan kebijakan pemerintah lokal (Santosa et al, 2013). Amam dan Harsita (2019) menyebutkan bahwa pengembangan usaha ternak dapat mempengaruhi SDM peternak sapi perah.…”
Section: Pengembangan Usaha Ternak Sapi Perahunclassified